Show step by step and solve will mark brainly) 7h/12 – 4h/12=18/12

Question

Show step by step and solve will mark brainly) 7h/12 – 4h/12=18/12

0

Answers ( No )

    0
    2021-10-13T22:48:07+00:00

    Answer:

    h=6

    Step-by-step explanation:

    Rearrange the equation by subtracting what is to the right of the equal sign from both sides:

                        7*h/12-4*h/12-(18/12)=0

                     3

    Simplify   —

                     2

          h      h   3

     ((7•——)-(4•——))-—  = 0

         12     12   2

                h

    Simplify   ——

               12

            h           h      3

     ((7 • ——) –  (4 • ——)) –  —  = 0

           12          12      2

                      h

    Simplify   ——

                      12

            h     h     3

     ((7 • ——) –  —) –  —  = 0

           12     3     2

         Least Common Multiple:  12

    To calculate equivalent fraction , multiply the Numerator of each fraction, by its respective Multiplier.

      L. Mult. • L. Num.      7h

      ——————————————————  =   ——

            L.C.M             12

      R. Mult. • R. Num.      h • 4

      ——————————————————  =   —————

            L.C.M              12  

    Add the two equivalent fractions which now have a common denominator

    Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

    7h – (h • 4)     3h

    ————————————  =  ——

         12          12

     3h    3

     —— –  —  = 0

     12    2

     Find the Least Common Multiple

         The left denominator is :       4

         The right denominator is :       2

         Least Common Multiple:  4

    Making Equivalent Fractions :

    Rewrite the two fractions into equivalent fractions

      L. Mult. • L. Num.      h

      ——————————————————  =   —

            L.C.M             4

      R. Mult. • R. Num.      3 • 2

      ——————————————————  =   —————

            L.C.M               4  

    Adding fractions that have a common denominator :

    h – (3 • 2)     h – 6

    ———————————  =  —————

         4            4  

     h – 6

     —————  = 0

       4  

    Now,to get rid of the denominator, multiply both sides of the equation by the denominator.

     h-6

     ——— • 4 = 0 • 4

      4

    Now, on the left hand side, the  4  cancels out the denominator, while, on the right hand side, zero times anything is still zero.

      h-6  = 0

    Solve  :    h-6 = 0

     h = 6

     

Leave an answer

Browse
Browse